Challenges of IFRS implementation in emerging economies: The case of Lebanon - Sadaka, Sami F. (2022)
IFRS and their implementation are being associated with globalisation and the increasing influence of global institutions such as the World Bank. This article investigates the challenges of IFRS implementation in Lebanon, an Asian, Middle-Eastern, and an emerging economy. The findings are theoretically framed within the system, society and dominance (SSD) framework. The analysis demonstrates that system and dominance effects have driven the initial phase of IFRS implementation in Lebanon. However, societal factors have created challenges to this implementation. The article proposes a framework that categorises these challenges as schisms within the local field of accounting, associated with practice, education, and regulation.